Does Level of Response to SI Joint Block Predict Response to SI Joint Fusion?. Issue 1 (April 2016) - Polly, David W.; Cher, Daniel; Whang, Peter; Frank, Clay; Lockstadt, Harry; Harvey, Charles; Sembrano, Jonathan
Introduction: The threshold percent pain relief required to diagnose sacroiliac joint (SIJ) dysfunction during a diagnostic SIJ block (SIJB) is not known. Although there is no gold standard, one reference standard is response to definitive treatment. Methods: Subgroup analysis of 320 subjects in two prospective trials of SIJ fusion: INSITE (NCT01681004) a randomized trial versus nonsurgical management (NSM) and SIFI (NCT01640353), a singlearm study. All participants were diagnosed with SIJ dysfunction via history (buttocks/leg pain and a positive Fortin finger test), at least 3 positive provocative physical examination signs, and a standardized diagnostic SIJB using fluoroscopically guided injection of local anesthetics in the target joint with a reduction of at least 50% in pain at 30 or 60 minutes after SIJB. The degree of improvement in VAS SIJ pain and Oswestry Disability Index (ODI) scores, expressed as absolute or percentage improvement from baseline, was correlated with the average acute improvement in SIJ pain during the SIJB, calculated as per Cohen et al. Results: The average pain reduction during the first hour after SIJB was 79.3%. Pain reduction during block was unrelated to standard demographic predictors. Six months after SIJ fusion, the mean VAS SIJ pain reduction was 50.9 (28.6) points and the mean ODI reduction was 24.6 (20.5) points. SIJ pain and ODI reductions at 12 months in the SIJ fusion group were 50.8 (29.2) and 25.8 (20.5) points, respectively. There was little correlation in 6 or 12month improvements in SIJ pain or ODI with average reduction in pain during SIJB. In the SIJF group, the proportion of subjects achieving meaningful reductions in SIJ pain and ODI scores did not vary by average response during SIJB ( p = 0.8407 and 0.3069, respectively for 6 month changes, and p = 0.6368 and 0.5913). Similarly, response during SIJB did not predict the proportion of patients with followup pain scores < 30 or ODI < 20. Conclusion s. In this study of > 300 patients with carefully diagnosed with SIJ dysfunction, the degree of improvement in acute pain during an SIJB did not predict 6month improvements in VAS SIJ pain or ODI score. Based on our study, a 50% acute pain reduction threshold during SIJB was resulted in excellent postsurgical results. The use of overly stringent selection criteria for determining which patients should undergo SIJF may serve to withhold a beneficial procedure from a substantial number of patients with SIJ dysfunction.